(Na)dzieje Wandy Romer jako przykład tekstualizacji wielojęzyczności – rekonstrukcja sensu w świetle semantyki interpretacyjnej Françoisa Rastiera - Karolina Kowalcze-Franiuk (Pl.it)
The article, representing the paradigm of humanistic linguistics, deals with the novel (Na)dzieje 1939–2019, a linguistic autobiography by Wanda Romer, a Polish wartime emigrant in Italy. The paper analyses two layers of the novel – its content and form, tied together by seven, cooccurring and entering into dialogue languages: Polish, French, English, German, Italian, Russian and Romanian. The purpose of the article is to show the novel as an example of the textualization of the author’s multilingualism and her autobiographical narrative of a metaphorical return to Polishness. The article reconstructs the genesis and meaning of the co-occurrence of languages in the novel through the method of linguistic biography and by means of François Rastier’s interpretive semantics, which is one of the possible tropes for interpreting the novel.